Inflammatory response and peritoneal contamination after transrectal natural orifice specimen extraction (NOSE) versus mini-laparotomy: a porcine in vivo study - Senft, Jonas; Dröscher, Tilman; Gath, Philip; Müller, Philip C.; Billeter, Adrian; Müller, Beat P.; Linke, Georg R. (Surgical endoscopy and other interventional techniques, 2018)
BackgroundTransrectal natural orifice specimen extraction (NOSE) avoids abdominal organ retrieval during laparoscopic procedures and may reduce surgical trauma. However, this has not been proven clinically and transrectal peritoneal contamination is feared to cause infectious complications. This experimental study was designed to evaluate inflammatory response and peritoneal contamination after transrectal NOSE versus mini-laparotomy.Methods24 German Landrace pigs underwent transrectal NOSE (N = 12) or mini-laparotomy (N = 12) for standardized extraction of water-instilled balloon. Blood samples were taken for analysis of leucocytes, CRP, IL-6, IL-10, and TNFα at 6, 12, 24, 48, 72 h as well as 7 and 14 days postoperatively. After 14 days laparoscopy was performed to inspect the abdomen and for microbiological swab sampling.ResultsLeucocytes were higher in the NOSE group at 72 h (19.3 ± 3.9/nl vs. 15.8 ± 4.2/nl, p = 0.046). IL-6 was lower in the NOSE group at day 7 (165 ± 100/nl vs. 306 ± 70/nl, p = 0.030). No difference was found comparing inflammatory parameters at all other time points. No difference was found regarding peritoneal contamination, which was 58.3% (7/12) in the NOSE group and 41.7% (5/12) in the MiniLap group (p = 0.414).ConclusionsThe results suggest a pronounced acute inflammatory response after transrectal NOSE compared to mini-laparotomy, while late cytokine response seems to be less after transrectal NOSE, which may reflect less intense wound healing process. Using standardized rectal decontamination and endolumenal colon occlusion transrectal NOSE seems to be safe and comparable to mini-laparotomy with regard to peritoneal contamination. Clinical evidence is needed now to weight transrectal NOSE against mini-laparotomy during laparoscopic surgery.